(untitled) (Prostor, 2023)
The complex of medical institutions of the 1920s on Zeleni brijeg (Green Hill) in Zagreb was built as a kind of a stronghold of the pioneering programme of new institutional forms of primary health care, as conceived by Andrija Štampar and his associates. The Institute of Epidemiology, which was originally supposed to be built according to Drago Ibler›s project (1922), but it was later rejected. The construction of the Institute began in the autumn of 1924, according to the plans by Vasily Mikhailovich Androsov, one of the Russian architects employed in the Architectural Department of the Ministry of Construction in Belgrade, probably after a closed competition, hastened by the threat that substantial funds allocated by the Ministry of Public Health, the Hygiene Section of the League of Nations, and above all the Rockefeller Foundation, would be lost. An Androsov design also replaced another avant-garde design of Croatian and Yugoslav modernism: due to direct intervention by King Alexander Karađorđević, Androsov’s design for the Palace of the Main Post Office in Belgrade, in the spirit of academic mannerism, was chosen and built instead of Josip Pičman’s design that had taken the first prize in the relevant competition. Hence the title of this article, which draws attention to the creator of a block of buildings of medical institutions, the interesting history of which can now be discussed on the basis of more information.